Tingkat Popularitas dan Profitabilias Menu A’la carte Melalui Metode Menu Engineering Di Restaurant Rajo Makan Hotel Daima Kota Padang - Desi Lestari Tili (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
The purpose of this research was to find out1how much the level of popularity and profitability of the a’la carte menu is through the engineering method at restaurant Rajo Makan at Daima Hotel in Padang City. The type of this research is descriptive quantitative research. This research used population sampling with 110 menus a'la carte of food and beverages as samples during June 2018. Techniques Data collection used the method of documentation, observation and interviews. The sources of data were from documents which are available documents.Then, data analyzedby using the engineering work sheet menu and group it through four box analysis. The results of the study showed that: from the 110 menus a'la carte foods and drinks at rajo makan restaurant during June 2018 in the four box analysis category classification. There are 18 menus classified as stars, 27 menus a'la carte classified as plowhorse categories, 47 menus a'la Carte belongs to the puzzle category, 18 a'la carte menus are classified as dogs.